The birth of a new industry: Entry by start-ups and the drivers of firm growth. The case of encryption software - Marco S. Giarratana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
The paper analyses the birth of the Encryption Software Industry (ESI), a new niche in the software industry. Using a Chandlerian perspective, this work reports the main facts about firm entry and growth, with a particular focus on start-up strategies and actions. Since scale economies do not play a major role in ESI, the paper investigates the different sources of firm competitive advantages. This work shows that innovation and product differentiation, along with investments in co-specialised assets, are variables strongly correlated to young firm probability to survive and grow. In so doing, we have collected highly detailed information on product introduction, US patents granted, worldwide alliances and biographical data of firm founders.
Keywords: 330; Entry; Entrepreneurship; Innovation; Software; Markteintritt; Innovation; Softwareindustrie; Entrepreneurship-Ansatz; Unternehmensgründung; USA